Resistance inheritance of soybean to cercospora Sojina hara isolated from São Gotardo, MG, Brazil - Cordeiro, Antonio Carlos Centeno; Sediyama, Tuneo; Gomes, José Luiz Lopes; Sediyama, Carlos Sigueyuki; Reis, Múcio Silva (Pesquisa Agropecuaria Brasileira, 1992)
A monosporous, naturally infected culture isolated from soybean (Glycine max (L.) Merrill) cv. UFV-1, obtained at São Gotardo, MG, Brazil, was used to investigate its inheritance resistance to Cercospora sojina Hara. F1 and F2 progenies from crosses of Paraná X Bossier, Santa Rosa X Bossier, Santa Rosa X IAC-8, and F2 progenies from crosses Santa Rosa X Cristalina and Paraná X Cristalina, artificially infected with a concentration of 3 X 104 conidia per milliliter, were evaluated under greenhouse condition. Notes varying from 1,0 (symptom absence) to 5,0 (maximum infection) were given to the most infected leaf per plant, considering resistance reaction the notes from 1,0 to 3,0 and susceptibility from 4,0 to 5,0. The chi-square (X2) test was used to analyse the progenies segregation results. According to the results the resistance inheritance to C. sojina is probably controlled by three dominant genes: a principal one, that conditions resistance independently from the others; two complementary, that condition resistance when both dominants are present; and, susceptibility at any other combination.
Keywords: G1ycine max; isolated from culture; inoculation; inheritance of resistance; improvement